Aerosol particles during the Innsbruck Air Quality Study (INNAQS): The impact of transient fluxes on total aerosol number exchange. (October 2018) - von der Heyden, Lisa; Deventer, Malte Julian; Graus, Martin; Karl, Thomas; Lamprecht, Christian; Held, Andreas
Abstract: Air quality in the city of Innsbruck, Austria, is affected by transalpine traffic and mountainous terrain, which is characterized by a pronounced mountain – valley wind system often favouring high pollution levels. To contribute to a better understanding of urban air pollution mechanisms in an Alpine valley, eddy covariance (EC) measurements with a condensation particle counter (CPC) were performed at an urban site in Innsbruck in the framework of the Innsbruck Air Quality Study (INNAQS). Emission fluxes of 10.6⋅10 7  m −2  s −1 (median) were observed during daytime and up-valley flow, whereas fluxes during reversal periods of the valley wind system were more variable and partly negative. Sporadic gust-like motions of vertical wind and concurrently measured large changes in particle number concentration (termed particle gusts) significantly biased total particle fluxes, reflecting, however, rather local fluxes at the measurement height. The particle gust events were identified by applying the median absolute deviation (MAD) method to particle fluxes. The particle flux was reconstructed by means of a continuous wavelet transform (CWT) to confirm the validity of the EC calculations during particle gusts. Their origin could not clearly be identified, but they indicate the presence of poorly mixed air parcels which are strongly enriched with particles. Due to the episodic yet large contribution to particle fluxes in Innsbruck, the potential impact of particle gusts on turbulent particle exchange should also be evaluated at other urban and non-urban sites. Highlights: Quantification of particle fluxes at a site characterized by urban and alpine terrain. So-called particle gusts strongly increase local fluxes at this site. Good agreement of fluxes calculated by eddy covariance and wavelet transform confirm validity of results.